Instrumentalidade e Consistência do Direito na Perspectiva Sistêmica de Niklas Luhmann - Cerbaro, Rodolfo Henrique (2024)
This article explores the dichotomy faced by legal practitioners when considering whether the legal system should be seen as an object of study in search of internal logical consistency or as an instrument to guarantee order and social pacification. This question raises two paradigms that permeate legal thought and require careful evaluation: instrumentality and consistency. The discussion aims to present the relevance of sociologist Niklas Luhmann's systems theory to understand the two paradigms in the legal context. By exploring these themes, the article seeks to provide theoretical insights into how legal practitioners can interpret and balance instrumentality and consistency in their professional practices.